Annealing and etching treatments on ZnO:Al films deposited by middle frequency sputtering at room temperature. Issue 7 (14th April 2014) - Zhu, H.; Mai, Y.; Lai, B.; Wan, M.; Huang, Y.; Zhang, L.
<x xml:space="preserve">Abstract</x> Large area aluminum doped zinc oxide films (ZnO:Al) were prepared at room temperature in a magnetron sputtering system. The optical and electrical properties as well as etching behaviors and surface structures of ZnO:Al films before and after etching and annealing treatments were systematically investigated. It is found that the ZnO:Al films prepared at room temperature without annealing show a low total transmission. The carrier concentration seems to be inhomogeneous in the films and increases along the growth direction, which can be derived from the shift of plasma resonance wavelength of the etched ZnO:Al films. The annealing treatment leads to a re‐crystallization of the ZnO:Al films and a further increase in carrier concentration. Excess annealing treatment would lead to an increase in resistivity. The etching of annealed ZnO:Al films results in different surface structures varying from hill‐like to small crater‐like shapes with the increasing annealing treatment duration in this case.